Health literacy of people living with mental illness or substance use disorders: A systematic review. Issue 6 (30th November 2020) - Degan, Tayla J.; Kelly, Peter J.; Robinson, Laura D.; Deane, Frank P.; Smith, Anna M.
Abstract: Aim: Health literacy is one's ability to use cognitive and social skills to access, understand and appraise health information. Despite poor health outcomes of people living with mental illness there is limited research assessing their health literacy. This systematic review aims to synthesise research on health literacy rates, conceptualizations, and outcomes of people living with mental illness, including substance use disorders. This will provide insights into how health literacy might be targeted to reduce these health inequities. Methods: A search of published literature in multiple databases up until February 2019 was conducted. One reviewer screened the titles, abstracts and keywords of identified publications and the eligibility of all full‐text publications were assessed for inclusion along with a second reviewer. Both reviewers independently rated the quality of the included studies. Results: Fourteen studies were included in the review. Rates and measures of health literacy varied. Low health literacy and health literacy weaknesses were identified. There is a lack of research on the relationship between health literacy and other outcomes, particularly health service engagement. Conclusion: The review highlights the high rates of low health literacy within this population compared with general populations. Most studies used a functional health literacy measure, despite its limitations, with only a few using multidimensional measures. Overall, there is limited research examining the impact that this populations health literacy has on their recovery and how it affects them over time. The review emphasizes the importance of practitioners assessing and targeting health literacy needs when working with this population.